A systematic review and meta-analysis of bovine brucellosis seroprevalence in Latin America and the Caribbean - Bonilla-Aldana, D. Katterine (2023)
Introduction: Bovine brucellosis is a significant public health problem in countries with economic and zoonotic implications. Although relevant, there are no previous systematic reviews about bovine brucellosis in Latin America. Methods: We performed a systematic literature review in five data-bases to assess the seroprevalence of Brucella in cattle. A meta-analysis with a random-effects model was performed to calculate the pooled prevalence and 95% confidence intervals (95%CI). In addition, measures of heterogeneity (Cochran's Q statistic and I2 test) were reported. Results: The literature search yielded 3,403 articles, of which 65 studies were fully valid for analysis. The pooled seroprevalence for Brucella in bovine (n ​= ​46,883,177) was 4.0% (95%CI: 3.0%–5.0%; p ​< ​0.001), and Venezuela was the country with the highest prevalence (16.0%). By regions, the highest seroprevalence is in Central America and the Caribbean islands (8.0%,95%CI: 3.0%–15.0%; p ​< ​0.001, I2 ​= ​99.85). Conclusions: Some countries reported still relevant seroprevalences of bovine brucellosis, especially at the Central America and Caribbean islands. Multiple factors may influence the survival and spread of pathogens in the environment; farms located in regions bordering forest areas, in areas of difficult access to the veterinary service; extensive beef herds raised at pastures with different age and productive groups inter-mingled, and minimal concerns regarding hygiene practices and disease prevention measures. Bovine brucellosis has not been eliminated and needs to be considered with new tools for prevention and control, especially being a zoonosis.